2008
DOI: 10.1152/jn.00866.2007
|View full text |Cite
|
Sign up to set email alerts
|

Trunk Sensorimotor Cortex Is Essential for Autonomous Weight-Supported Locomotion in Adult Rats Spinalized as P1/P2 Neonates

Abstract: Unlike adult spinalized rats, approximately 20% of rats spinalized as postnatal day 1 or 2 (P1/P2) neonates achieve autonomous hindlimb weight support. Cortical representations of mid/low trunk occur only in such rats with high weight support. However, the importance of hindlimb/trunk motor cortex in function of spinalized rats remains unclear. We tested the importance of trunk sensorimotor cortex in their locomotion using lesions guided by cortical microstimulation in P1/P2 weight-supporting neonatal spinaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 65 publications
7
28
0
Order By: Relevance
“…Improvement in limb placements during overground locomotion by both ipsilesional forelimbs and hindlimbs too may be driven by cortical plasticity. In the neonatally spinalized rats, sensorimotor cortex reorganizes to participate in overground locomotion (Giszter et al, 2008); in intact rats, the cortex is thought to have little role in this form of locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in limb placements during overground locomotion by both ipsilesional forelimbs and hindlimbs too may be driven by cortical plasticity. In the neonatally spinalized rats, sensorimotor cortex reorganizes to participate in overground locomotion (Giszter et al, 2008); in intact rats, the cortex is thought to have little role in this form of locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of anesthetic method (we used isoflurane as opposed to hypothermia), spinal transection surgery is largely as described in detail in Miya et al (1997) and Giszter et al (1998Giszter et al ( , 2008a. Neonates were placed under isoflurane anesthesia and maintained on an anesthetic plane (0.75%-2% mixed in oxygen), and sterile procedures were used throughout the surgery.…”
Section: Methodsmentioning
confidence: 99%
“…This was accomplished in a manner similar to Miya et al (1997) and Giszter et al (1998) by determining the proportion of autonomous hindlimb weight-supporting steps (%WSS) taken compared with the sum of hindlimb steps attempted (i.e., sum of weight-supported and non-weight-supported steps) (Miya et al, 1997;Giszter et al, 1998). The classification we used here was based on observations (Giszter et al, 2008a; see Materials and Methods) that most NTX rats showed either good consistent weight-supported stepping of Ͼ50%WSS (weight-supporting NTX rats or WS, usually ϳ20% of rats prepared) or poor weight-supported stepping of Ͻ50%WSS, which was often accompanied with frequent hindlimb scissoring action (NWS) (Giszter et al, 2008a) (usually ϳ80% of rats prepared). In prior work, the WS and NWS rats generated after neonatal spinal transection differed in a range of ways, with a "no-man's land" between the function levels of 20%-25%WSS and 45%-50% or better WSS (Miya et al, 1997;Giszter et al, 1998Giszter et al, , 2007.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations